Effects of individualized administration of folic acid on prothrombotic state and vascular endothelial function with H-type hypertension: A double-blinded, randomized clinical cohort study. Issue 3 (21st January 2022) - Zhang, Song; Wang, Tianxun; Wang, Huaiqi; Tang, Jianping; Hou, Ailin; Yan, Xiaoling; Yu, Baozhong; Ran, Shuangming; Luo, Min; Tang, Ying; Yang, Ruohan; Song, Dongsheng; et al.
Abstract: Background: Hypertension and hyperhomocysteinemia (HHcy) have long been associated with adverse cardiovascular and cerebrovascular health outcomes. This study evaluated the effect of individualized administration of folic acid (FA) on homocysteine (Hcy) levels, prothrombotic state, and blood pressure (BP) in patients with H-type hypertension (combination of HHcy and hypertension). Methods: In this double-blinded, randomized clinical cohort study, 126 patients with H-type hypertension who were treated at our hospital were randomly divided into treatment and control groups (n = 55 each). The control group was treated with oral levamlodipine besylate tablets 2.5 mg and placebo, once a day (in the morning). The treatment group was first treated with oral levamlodipine besylate 2.5 mg and FA tablets 0.8 mg, once a day (in the morning), for 12 weeks. Then, in a second 12-week phase, the FA dose was adjusted using the methylene tetrahydrofolate reductase C677 polymorphism genotype. The levels of Hcy and coagulation factors, prothrombotic state parameters, BP, and adverse drug reactions were compared between the 2 groups. Results: Pretreatment general patient characteristics, including Hcy levels, were similar between the 2 groups ( P  > .05). BP and prothrombotic status did not differ before and after the first phase of treatment ( P  > .05). However, Hcy and endothelin-1 (ET-1) levels decreased, while nitric oxide levels increased significantly in the intervention group ( P  < .05). In the second phase, after 3 months' treatment with an FA dose adjusted according to methylene tetrahydrofolate reductase C677T genotype, the Hcy and ET-1/NO levels were significantly decreased in the intervention group and were lower than those after the first treatment phase and lower than in the control group ( P  < .01). BP, D-dimer levels, and fibrinogen scores were significantly lower after the second treatment phase ( P  < .01). There was no significant difference in the incidence of adverse drug reactions between the 2 groups ( P  > .05). Conclusions: Individualized administration of FA tablets can effectively reduce BP, and Hcy and coagulation factor levels, and significantly improve prothrombotic status in patients with H-type hypertension.